The acceptance of eTPP reporting system by using TAM Model / Mohd Hafizan Musa [et al.] - Musa, Mohd Hafizan; Othman, Ahmad Kamalrulzaman; Wan Zakaria, Wan Mohd Farid; Mohamad Khalid, Rusnani; Sokman, Yusnita (Universiti Teknologi MARA, Negeri Sembilan, 2018)
Technological innovations are significant in human and professional life. A new online correction and prevention system called eTPP to replace old traditional system has introduced new major changes in the reporting process. Therefore, this study was carried out to determine the level of user's acceptance towards eTPP and to investigate the factors that influence user's behavioural intentions to use eTPP in UiTM Cawangan Johor, Kampus Segamat. A Technology Acceptance Model (TAM) was employed as a conceptual framework to investigate the factors that influence users' acceptance to use eTPP. To test the model, data were collected from 44 respondents from various departments in UiTM Cawangan Johor, Kampus Segamat. Questionnaires were distributed to collect primary data from the respondents about their acceptability of eTPP. The results were presented through multiple regression analysis and supported by mediating analysis (Preacher and Hayes, 2008; Baron and Kenny, 1986), whereby it showed consistent mediating result with the regression result. The overall finding of the study showed that the perceived ease of use was the main factor influencing eTPP acceptance among the users.